G-category versus orbifold category - Ángel, Andrés; Colman, Hellen (Topological Methods in Nonlinear Analysis, 2023)
We present a comparative study of certain invariants defined for group actions and their analogues defined for orbifolds. In particular, we prove that Fadell’s equivariant category for G-spaces coincides with the Lusternik-Schnirelmann category for orbifolds when the group is finite.